Carbetocin at Elective Cesarean Section: A Sequential Allocation Trial to Determine the Minimum Effective Dose in Obese Women. Issue 1 (24th March 2021) - Drew, T.; Balki, M.; Farine, D.; Ye, X.Y.; Downey, K.; Carvalho, J.C.A.
Abstract : ( Anaesthesia . 2020;75:331–337) Uterotonics are widely used in cesarean deliveries to prevent postpartum hemorrhage, which can cause maternal death or severe morbidity. Obesity, among other factors, has been implicated as a contributing factor to the rise in atonic postpartum hemorrhage in developed countries. The use of carbetocin, a synthetic oxytocin analogue, is associated with a reduced need for uterotonics in cesarean deliveries. While previous studies found 90% effective dose (ED90 ) of carbetocin for women with a body mass index (BMI) <40 kg/m 2, none have addressed the ED90 for obese women. This study aimed to find the ED90 of carbetocin in women with a BMI ≥40 kg/m 2 undergoing elective cesarean delivery.